INFLUENCE OF IMMOBILIZED FORMS OF SODIUM HYPOCHLORITE ON THE IMMEDIATE AND LONG-TERM RESULTS OF TREATMENT OF THE PATIENTS WITH DIFFUSE PERITONITIS - B. S. Sukovatykh; Yu. Yu. Blinkov; K. G. Makienko (Вестник хирургии имени И.И. Грекова)
An analysis of complex examination and results of treatment was made in 290 patients with diffuse peritonitis. The patients were divided into two groups according to way of sanation of the abdominal cavity. The sanation with 0,03% aqueous solution of sodium hypochlorite was used for the first group of 155 patients. The immobilized forms of sodium hypochlorite in carboxymethyl cellulose gel were applied in the second group. The rate of postoperative complications was decreased on 15,4%, the lethality - on 8,2% in the case of application of the immobilized forms of sodium hypochlorite. The developed technology allowed increasing of physical component of life quality of the patients in 1.3 times, though it didn’t influence on psychical component.